CONTRIBUTION TO IMPULSIVE EQUATIONS - Zohra, Berrabah Fatima (European Scientific Journal, ESJ, 2014)
In this paper, we show the validity of the method of upper andlower solutions to obtain an existence result for a first order impulsive differential equations with variable moments. In this paper we will consider the following system of differential equations with impulses at variable times.